(untitled) (Contemporary Journal of Social Science Review, 2026)
This study investigates the impact of parental socio-economic status (SES) and parent–teacher collaboration (PTC) on the academic performance (AP) of secondary school students. Grounded in a quantitative research design, a two-stage random sampling approach was used to obtain data from a sample of 200 students, along with their parents and teachers. Data were gathered through a self-developed instrument comprising demographic information, SES indicators, and structured surveys for parents and teachers. Inferential statistical techniques, including linear regression, Pearson correlation, and multiple regression models, were applied to analyze the data. The findings reveal that both SES and PTC exert a statistically significant influence on students’ academic performance. Furthermore, a moderate positive association was identified between the two independent variables, namely SES and PTC. The inclusion of socio-economic status as a mediating variable revealed that the association between parent-teacher collaboration and academic performance remains positive and significant, albeit with a reduced coefficient. These results highlight the combined role of socioeconomic factors and collaborative engagement between parents and teachers in shaping educational outcomes. It suggests that schools should implement regular parent–teacher interactions, provide parental guidance programs, and develop flexible communication strategies, particularly to support families from lower socioeconomic backgrounds, to enhance students’ academic outcomes.